Efektivitas Pemberian Tablet Fe dan Jus Tomat terhadap Peningkatan Kadar Hb pada Ibu Hamil - Mayang Wulan; Sri Juliani; Nuriah Arma; Mila Syari (Poltekkes Kemenkes Palu, 2021)
Introduction: Pregnant women are anemic. No one has ever consumed tomato juice during pregnancy because they do not know the benefits of tomato juice. There has never been any counseling regarding the handling of increased Hb levels using tomato juice. The aim this research is to determine the effectiveness of giving Fe tablets and tomato juice to increase hemoglobin levels in pregnant women in the working area of ​​the West Delitua Sub-district Health Center. Methods: Quasi experiment one group design with pre and post-design. The total population is 30 respondents, and the sample using purposive sampling is as many as 20 respondents. The data used are primary and secondary. Data analysis using univariate and bivariate using non-parametric with Wilcoxon test. Results: A total of 20 pregnant women (100%) experienced mild anemia before giving Fe tablets and tomato juice, and after being given Fe tablets and tomato juice, 15 people (75%) experienced mild anemia from the Wilcoxon test that has carried out, it knows that Asym.Sig, (2-tailed) is 0.000. Conclusion: There is an effect of giving fe tablets and tomato juice on increasing hemoglobin levels in pregnant women in the Work Area of ​​the West Delitua Sub-district Health Center. I hope that pregnant women will increase their knowledge about the benefits of foods containing vitamin C, especially tomatoes, which are beneficial for anemia and can maintain health, especially during pregnancy.